Information technologies as a tool of pharmaceutical data management - K. A. Koshechkin; E. M. Rychikhina (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article analyses international experience of information technology use in pharmaceutical data management. It investigates the possibility of using CALS/PLM-technologies for IT-based management of pharmacy-related activities as exemplified by the introduction of the eCTD format of the registration dossier. The authors provide recommendations that could facilitate the Russian regulatory system’s transition to a similar format and help use this format to create the common medicines market within the Eurasian Economic Union. A brief description of the modules included in the common technical document and their content is provided, as well as general principles of developing an electronic version of the present format. The use of a single electronic format for dossier submission will make it possible to automatically control the completeness of submitted materials and to integrate information systems used by manufactures and regulatory authorities.